2003
DOI: 10.1073/pnas.0237165100
|View full text |Cite
|
Sign up to set email alerts
|

Bimodal signal requisite for agonistic behavior in a dart-poison frog,Epipedobatesfemoralis

Abstract: Animal acoustic signals play seminal roles in mate attraction and regulation of male spacing, maintenance of pairbonds, localization of hosts by parasites, and feeding behavior. Among vertebrate signals, it is becoming clear that no single stereotyped signal feature reliably elicits species-specific behavior, but rather, that a suite of characters is involved. Within the largely nocturnal clade of anuran amphibians, the dart-poison frog, Epipedobates femoralis, is a diurnal species that physically and vigorous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
200
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 235 publications
(208 citation statements)
references
References 25 publications
5
200
0
2
Order By: Relevance
“…As long as the speciesspecific advertisement call is broadcast at a level Ͼ68 dB sound pressure level measured at the position of the focal male (12) and the vocal-sac pulsations are synchronous with the acoustic stimulus, fighting behavior ensues (7). Thus, a protocol has been established in which simultaneous and colocalized bimodal cues evoke aggressive behavior in territorial male E. femoralis (7). Taking advantage of this robust aggressive response to simulated intruders into their territory, we tested two new related hypotheses concerning aggressive behavior in this species.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…As long as the speciesspecific advertisement call is broadcast at a level Ͼ68 dB sound pressure level measured at the position of the focal male (12) and the vocal-sac pulsations are synchronous with the acoustic stimulus, fighting behavior ensues (7). Thus, a protocol has been established in which simultaneous and colocalized bimodal cues evoke aggressive behavior in territorial male E. femoralis (7). Taking advantage of this robust aggressive response to simulated intruders into their territory, we tested two new related hypotheses concerning aggressive behavior in this species.…”
mentioning
confidence: 99%
“…Increasing the spatial disparity between a voice's actual source and its apparent source by Ͼ30°or delaying the auditory cue relative to the visual cue by Ͼ200 ms reduces the realism of the illusion (6) Many anuran amphibians also produce simultaneous bimodal advertisement signals in which the call is accompanied by a conspicuous visual cue: vocal-sac inflation. ** For example, it has been shown that fighting behavior in the diurnal dart-poison frog Epipedobates femoralis can be experimentally evoked with an electromechanical model frog (EMF) broadcasting bimodal cues consisting of the synthetic advertisement call coupled with simultaneous vocal-sac pulsations (7). As long as the speciesspecific advertisement call is broadcast at a level Ͼ68 dB sound pressure level measured at the position of the focal male (12) and the vocal-sac pulsations are synchronous with the acoustic stimulus, fighting behavior ensues (7).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, not all tested males responded aggressively to those differentiated calls, hinting at a complex scenario of conspecific acoustic signal recognition. Previous studies using A. femoralis synthetic calls found that extreme variations in their temporal (note duration and inter-note silent intervals) and spectral (frequency) properties influence male-to-male intraspecific recognition and aggressive territorial responses (Amézquita et al, 2005;Göd et al, 2007), which can be also modulated by intra and interspecific visual stimuli (Narins et al, 2003;Luna et al, 2010). However, the species has a wide acoustic recognition space when compared to evolutionarily related species (Amézquita et al, 2011).…”
Section: Discussionmentioning
confidence: 98%
“…Although many animals respond to video images, some researchers have elected to capitalize on recent technological advances in robotics to develop realistic models that can be deployed to study multimodal communication (16).…”
Section: Multimodal Communicationmentioning
confidence: 99%